2017
DOI: 10.2139/ssrn.3047015
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Degradation, ICT and Inclusive Development in Sub-Saharan Africa

Abstract: (ii) ICT interacts with CO 2 intensity to negatively affect inclusive human development and (iii) the net effect on inclusive human development is positive from the complementarity between mobile phones and CO 2 emissions per capita. Conversely, we also establish evidence of net negative effects. Fortunately, the corresponding ICT thresholds at which these net negative effects can be completely dampened are within policy range, notably: 50 (per 100 people) mobile phone penetration for CO 2 emissions from liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…On the front of mismanagement, consistent with the attendant literature (Anyangwe, 2014; Asongu et al., 2017, 2018; Odhiambo, 2010, 2014a), the energy sector of many countries in SSA is not being managed properly, especially when it pertains to less investment in renewable energy and more allocation of funds to the subsidization of fossil fuels. It is worthwhile to emphasize that economic prosperity in the last two centuries has been fundamentally reliant on energy availability which is indispensable for economic processes, inter alia : production, distribution and consumption activities (Odhiambo, 2009a, 2009b, 2014b).…”
Section: Introductionmentioning
confidence: 84%
“…On the front of mismanagement, consistent with the attendant literature (Anyangwe, 2014; Asongu et al., 2017, 2018; Odhiambo, 2010, 2014a), the energy sector of many countries in SSA is not being managed properly, especially when it pertains to less investment in renewable energy and more allocation of funds to the subsidization of fossil fuels. It is worthwhile to emphasize that economic prosperity in the last two centuries has been fundamentally reliant on energy availability which is indispensable for economic processes, inter alia : production, distribution and consumption activities (Odhiambo, 2009a, 2009b, 2014b).…”
Section: Introductionmentioning
confidence: 84%
“…In other words, the IHDI also takes into consideration the manner in which the three underlying achievements are distributed within the population. (Asongu et al., 2017: 355)CO 2 emission per capita is used to measure environmental pollution or the policy syndrome, in line with recent environmental degradation literature (Asongu, 2018b). The policy variables are six main governance indicators highlighted above.…”
Section: Methodsmentioning
confidence: 99%
“…(ii) As documented in recent literature, the ramifications of fossil fuel consumption would be most detrimental in SSA (Asongu et al., 2017; Huxster et al., 2015; Kifle, 2008). This is essentially because, inter alia: carbon dioxide emissions (CO 2 ) constitute about 75% of greenhouse gas emissions in the world (Akpan and Akpan, 2012; Asongu et al., 2018).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the abundant natural resources that can be used to advance human development and quality of life, sub‐Saharan Africa (SSA) remains the region with the worst human capital foundations (Asongu, Le Roux, & Biekpe, 2017; Davis, 2017). For instance, the transition from the millennium development goals (MDGs) to SDGs showed that SSA remains a region with the largest number of people living in extreme poverty—about 389 million—and accounts for more than half of the total number of the global poor (World Bank, 2015).…”
Section: Introductionmentioning
confidence: 99%